(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
Based on the assumption that the sacred territory is inseparable from the body, that is, for the religious experience to reach the epiphany / hierophany, it is necessary to connect bodies with their center of the world (ELIADE, 1957, 2019), we seek to problematize the context of the deterritorialization of bodies from their sacred space, in the face of a crisis situation that makes liturgical practice impossible - in the case discussed, the COVID-19 pandemic of the 2020-21 biennium and its impacts on the religious practice of Umbanda practitioners. We launched some questions about how these disembedded bodies (GIDDENS, 1991), as a form of identity resistance, exercise their liturgy in an online environment, even with the fragmentation of the egregore composed of spiritual entities, mediums, and consultants. The object chosen to discuss the topic are the online liturgies (giras) of the Adérito Simões channel, on the YouTube platform, broadcast between 2020 and 2021.